2018
DOI: 10.1002/adma.201705605
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Self‐Assembling Micellar Depots that Can Actively Trap and Passively Release NO with Long‐Lasting Activity to Reverse Osteoporosis

Abstract: Treatment with exogenous nitric oxide (NO) donors is regarded as being effective against osteoporosis. However, NO has a short half-life, limiting its clinical usefulness. To overcome this limitation, an injectable microparticle (MP) system is developed that consists of phase-change materials capric acid (CA) and octadecane, and encapsulates a NO donor. The therapeutic efficacy of the MPs is evaluated in ovariectomized (OVX) rats with osteoporosis. Upon subcutaneous administration, the MPs undergo a phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…After incubating 7.5 × 10 3 cells in each well of a 48-well plate for 24 h, the culture medium was replaced with αMEM supplemented with 10% FBS, 50 µg/mL ascorbic acid, 5 mM β-glycerophosphate, and test MPs. The cells were then cultivated in 1% oxygen for 20 days (Lin et al, 2018). The culture media together with the test MPs were replaced every 3 days throughout the entire experimental course.…”
Section: Osteogenic Differentiation Of Mc3t3-e1 Cellsmentioning
confidence: 99%
“…After incubating 7.5 × 10 3 cells in each well of a 48-well plate for 24 h, the culture medium was replaced with αMEM supplemented with 10% FBS, 50 µg/mL ascorbic acid, 5 mM β-glycerophosphate, and test MPs. The cells were then cultivated in 1% oxygen for 20 days (Lin et al, 2018). The culture media together with the test MPs were replaced every 3 days throughout the entire experimental course.…”
Section: Osteogenic Differentiation Of Mc3t3-e1 Cellsmentioning
confidence: 99%
“…The NO half-life was extended from 20.6 s in NONOate donor to 21.6 min from the micelles. In vivo studies in the osteoporosis rat model have shown decreased bone turnover and, therefore, thicker trabecular bones along with denser networks and lower marrow fat levels [ 157 ]. As illustrated in Figure 3 , the microparticles injected subcutaneously undergo a phase transition and form micellar depots that release NO from the donor.…”
Section: Lipid-based Delivery Systems In Regenerative Medicinementioning
confidence: 99%
“… In situ generation of NO from the micellar depots after phase transition in comparison to naked NO formed the NONOate donor [ 157 ]. …”
Section: Figurementioning
confidence: 99%
“…After that, ac onventional double-emulsion method was employed to fabricate the nanocapsules.D iethylenetriamine diazeniumdiolate (DETAN ONOate) was chosen as the NO-releasing donor, and its hydrolysis rate to release two NO molecules at acidic condition was much faster than that at neutral pH. [23] After that, in vitro pH-responsive property of NO-NCPs was observed by transmission electron microscopy (TEM) analysis.N O-NCPs exhibited spherical nanostructure with ad iameter of around 200 nm at pH 7.4 ( Figure 1A). In addition, the hydrodynamic diameters kept almost constant upon 48 hi nd iverse culture medium, displaying promising stability,w hich was favorable for storage and in vivo blood administration ( Figure S3).…”
Section: Fabrication Of No-ncpsmentioning
confidence: 99%